Multi-protein bridging factor 1(Mbf1), Rps3 and Asc1 prevent stalled ribosomes from frameshifting - Wang, Jiyu; Zhou, Jie; Yang, Qidi; Grayhack, Elizabeth J (eLife, 2018)
Reading frame maintenance is critical for accurate translation. We show that the conserved eukaryotic/archaeal protein Mbf1 acts with ribosomal proteins Rps3/uS3 and eukaryotic Asc1/RACK1 to prevent frameshifting at inhibitory CGA-CGA codon pairs in the yeast Saccharomyces cerevisiae. Mutations in RPS3 that allow frameshifting implicate eukaryotic conserved residues near the mRNA entry site. Mbf1 and Rps3 cooperate to maintain the reading frame of stalled ribosomes, while Asc1 also mediates distinct events that result in recruitment of the ribosome quality control complex and mRNA decay. Frameshifting occurs through a +1 shift with a CGA codon in the P site and involves competition between codons entering the A site, implying that the wobble interaction of the P site codon destabilizes translation elongation. Thus, eukaryotes have evolved unique mechanisms involving both a universally conserved ribosome component and two eukaryotic-specific proteins to maintain the reading frame at ribosome stalls.
Keywords: translation; frameshifting; ribosome; Rps3; Asc1/RACK1; Mbf1